Water absorption and dissolution behavior of film adhesives used in aircraft structures - Tetsuo YASUOKA (Nihon Kikai Gakkai ronbunshu, 2022)
In this study, the water absorption behavior of a film adhesive for aircraft use was experimentally investigated, and the formula of weight gain of the adhesive with water immersion was proposed and evaluated, comprised of a Fickian diffusion term and a dissolution term. A gravimetric analysis by immersing the thin plate adhesive specimens in water revealed the weight of the specimens increased linearly with the square root of time in the initial phase of water absorption, and then the weight decreased after passing a peak. That means Fickian diffusion was dominant in the initial phase but was not after the initial phase, which may be caused by dissoluting the adhesive. For the purpose of considering dissolution, a Nernst-Noyes-Whitney equation was introduced, and the model of dissolvable area decreasing of specimen surfaces was considered, then those and Fick’s law of diffusion were integrated as the formula of the weight gain of the adhesive with water immersion. The proposed formula was evaluated by the least-squares fitting using experimental data. As a result, the fitting curves were almost consistent with experimental data and successfully simulated the behavior, that is, Fickian diffusion was dominant in the initial stage of water absorption, and the weight of the specimens decreased after the initial stage.